Hardness and posting of foot orthoses modify plantar contact area, plantar pressure, and perceived comfort when cycling. Issue 7 (July 2018) - Bousie, Jaquelin A.; Blanch, Peter; McPoil, Thomas G.; Vicenzino, Bill
Abstract: Objectives: To evaluate the effects of hardness and posting of orthoses on plantar profile and perceived comfort and support during cycling. Design: A repeated measures study with randomised order of orthoses, hardness, and posting conditions. Methods: Twenty-three cyclists cycled at a cadence of 90 rpm and a perceived exertion rating of twelve. Contoured soft and hard orthoses with or without a medial forefoot or lateral forefoot post were evaluated. Plantar contact area, mean pressure and peak pressure were measured for nine plantar regions using the pedar ® -X system and represented as a percentage of the total (CA%, MP%, and PP% respectively). Perceived comfort and support was rated on a visual analogue scale. Results: The softer orthosis significantly increased CA% ( p = 0.014) across the midfoot and heel with a decrease in the toe region and forefoot. MP% ( p = 0.034) and PP% ( p = 0.012) were significantly increased at the mid and lateral forefoot with reductions in MP% at the midfoot and in PP% at the hallux and toes. Forefoot posting significantly increased CA% ( p = 0.018) at the toes and forefoot and decreased it at the heel. PP% was significantly altered ( p = 0.013) based on posting position. Lateral forefoot posting significantly decreased heel comfort ( p = 0.036). Conclusion: When cycling, a soft, contoured orthosis increased contact across the midfoot and heel, modulating forefoot and midfoot plantar pressures but not altering comfort or support. Forefoot postings significantly modified contact areas and plantar pressures and reduced comfort at the heel.